Etiological and predictive factors of pediatric urticaria in an emergency context - Leelawadee Techasatian; Pariwat Phungoen; Jitjira Chaiyarit; Rattapon Uppala (BMC, 2021)
Abstract Background Urticaria is common in pediatric population and is caused by various etiologies which usually differ among different age groups. The different etiologies require different management strategies. Thus, understanding detailed of the etiologies of urticaria in children would help pediatricians to perform appropriate initial treatment. Methods A cross-sectional epidemiological study of all patients aged under 18-year-old with the diagnosis of urticaria from any causes entered in the emergency department during January 1st, 2016 to December 31st, 2019 by collecting the data from the Health Object Program®, an authorized electronic medical records program, at the Srinagarind Hospital, Faculty of Medicine, Khon Kaen University, Thailand. Results There were total of 515 urticaria patients aged under 18 years old at the emergency department. The ages of patients ranged from 8 months to 18 years with a median age of 7 years (IQR 3.17-12.08). The majority of the patients were in the preschool-aged group (40.97%), followed by the school-aged (28.16%), adolescent (22.14%), and infant (8.74%). Six major etiologic categories were identified in the present study. The most common cause of urticaria was infection (51.26%), followed by idiopathic urticaria (34.37%), inhalants (6.99%), drugs (4.08%), foods (2.52%), and insect stings (0.78%). Conclusions Having underlying allergic diseases had a strong association with all identified causes of urticaria in the study population, of which, food and inhalation etiologies had a significant difference when compared to the other identified causes. The present study has found that infection was the most common cause of acute urticaria in children. This etiology (infection-induced urticaria) usually presents concurrent with fever, however, non-febrile symptoms were also presented. Therefore, in the pediatric population, pediatricians should always look for infection as the cause of urticaria even in patients without pyrexia.